Copyright in community law: recent decisions of the European court of justice and of the European Commission - Hoffman, Frank (Intellectual Property Research Unit, 2026)
"The fact that the European Community is seeking to assimilate the economies of the nine Member States does not mean that the cultural diversity of the Member States should be eliminated at the same time. Indeed, the merit of European culture is the variety of cultures and languages it contains, yet all within a broadly similar tradition. Because each Member State needs, for example, its own publishing industry, just as it needs its own television service, does not mean that there is a failure to integrate the Community." Memorandum on European Community law and copyright in literary works, submitted by the British Publishers Association, September 1980.